Key Features and Parameters in Arabic Grammar - Fassi Fehri, Abdelkader (Linguistik Aktuell/Linguistics Today, 2012)
In light of recent generative minimalism, and comparative parametric theory of language variation, the book investigates key features and parameters of Arabic grammar. Part I addresses morpho-syntactic and semantic interfaces in temporality, aspectuality, and actionality, including the Past/Perfect/Perfective ambiguity akin to the very synthetic temporal morphology, collocating time adverb construal, and interpretability of verbal Number as pluractional. Part II is dedicated to nominal architecture, the behaviour of bare nouns as true indefinites, the count/mass dichotomy (re-examined in light of general, collective, and singulative DP properties), the mirror image ordering of serialized adjectives, and N-to-D Move in synthetic possession, proper names, and individuated vocatives. Part III examines the role of CP in time and space anchoring, double access reading (in a DAR language such as Arabic), sequence of tense (SOT), silent pronominal categories in consistent null subject languages (including referential and generic pro), and the interpretability of inflection. Semantic and formal parameters are set out, within a mixed macro/micro-parametric model of language variation. The book is of particular interest to students, researchers, and teachers of Arabic, Semitic, comparative, typological, or general linguistics.